No tillage and cover crops in the Pampas, Argentina - Berhongaray, Gonzalo (2021)
The no-till review showed that carbon increases between 3 percent and 15 percent in the topsoil (0-20 cm) in the long term. Average over the experiments a 2.76 t/ha SOC increase was observed in no-till systems compared with tilled systems. The largest increases corresponded to soils from the semiarid portion of the region, and the SOC under tillage explained most of the SOC variation under no-till. The conversion of the whole Pampas cropping area to no-till would increase SOC by 74 MtC, about twice the annual C emissions from fossil fuel consumption of Argentina (40 MtC/yr). The review of field experiments with winter cover crop reflect that SOC content of the 0 20cm layer rose ca. 4 percent in fine-textured soils and 9 percent in coarser ones.